2019
DOI: 10.1186/s12864-019-6087-1
|View full text |Cite
|
Sign up to set email alerts
|

Α de novo 3.8-Mb inversion affecting the EDA and XIST genes in a heterozygous female calf with generalized hypohidrotic ectodermal dysplasia

Abstract: Background In mammals, hypohidrotic ectodermal dysplasia (HED) is a genetic disorder that is characterized by sparse hair, tooth abnormalities, and defects in cutaneous glands. Only four genes, EDA, EDAR, EDARADD and WNT10A account for more than 90% of HED cases, and EDA, on chromosome X, is involved in 50% of the cases. In this study, we explored an isolated case of a female Holstein calf with symptoms similar to HED. Results Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…Localizing precise inversion breakpoints can be informative in functional studies as they may directly impact gene structure, such as has been reported in cattle ( Escouflaire et al 2019 ) or gene expression; by disrupting regulatory elements. Similarly, analyzing sequences close to a breakpoint may highlight signatures accompanying inversions such as the inverted repeat reported in Atlantic Herring ( Pettersson et al 2019 ) and provide insight into mechanisms by which inversions arise.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Localizing precise inversion breakpoints can be informative in functional studies as they may directly impact gene structure, such as has been reported in cattle ( Escouflaire et al 2019 ) or gene expression; by disrupting regulatory elements. Similarly, analyzing sequences close to a breakpoint may highlight signatures accompanying inversions such as the inverted repeat reported in Atlantic Herring ( Pettersson et al 2019 ) and provide insight into mechanisms by which inversions arise.…”
Section: Resultsmentioning
confidence: 99%
“…Localising precise inversion breakpoints can be informative in functional studies as they may directly impact gene structure, such as has been reported in cattle (Escouflaire et al 2019) or gene expression; by disrupting regulatory elements.…”
Section: Chromosomal Inversionsmentioning
confidence: 99%
“…The density of hair follicles in the affected calves presented in this study was only slightly greater than in unaffected calves. This is dissimilar to a calf with ECTD1, which had five times more hair follicles than a control calf [ 10 ]—this might be due to using different skin sites (scalp vs. flank) for follicular counts in the two variants of ECTD1. Sebaceous glands in the herein studied calves were morphologically normal.…”
Section: Discussionmentioning
confidence: 98%
“…HED has been documented in mice, dogs, cattle and rats [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Our understanding of EDA-related anhidrotic ectodermal dysplasia is based in large part on the Tabby ( Eda T a ) mouse [ 11 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation